The Core Curriculum and Integration in Medical Education - Nikoo Yamani; Masoumeh Rahimi (Tabriz University of Medical Sciences, 2016)
Background: The current challenges that confront the medical education field have necessitated the need for transformation and revisions in curriculum design practices. In this regard, core curriculum development and integration are examples of such changes. The purpose of this study was to investigate the concepts of core curriculum and integration in the realm of medical education and to explore the relationship between these two concepts. Methods: This study is a narrative review article. In this study, databases such as Science Direct, Ovid, PubMed, SID, Magiran and Google Scholar were searched using keywords such as core curriculum, integration, medical education, curriculum design and curriculum. Results: The importance of meaningful learning, organized knowledge and practical knowledge for students of medical sciences requires planning of integrated curricula. This is more accentuated based on the increasing volume of knowledge, educational content, continuous changes in community needs, responsibility to meet those needs and the need for medical students to gain clinical competencies in their profession. Conclusion: The concepts of core curriculum and integration are very closely linked, with some of the experts in the field of curriculum planning considering integration as one of the forms of designing core curriculum. Indeed, both concepts were developed in response to the overload of knowledge, the need to teach and learn basic and clinical sciences together and the need to create meaningful learning.